Human Values : Correspondence Analysis of Attitudes of Young and Older People - Stanimir, Agnieszka (Analiza korespondencji w badaniu postaw osób młodych i starszych wobec wybranych aspektów życia społecznego, 2011)
The main purpose of this article is to show the possibilities of the application of correspondence analysis in indicating differences between young and older people in attitudes to major life values. The respondents represent many countries and they differ where cultural, social, demographical and political systems are concerned. Different techniques of correspondence analysis were used to identify interactions between variables. Simple correspondence analysis indicated geographical differences in perception of the most important features within each age group. Introduction of the doubled ratings into the study allowed to identify not only the best, but also the lowest rated features. At the same time the use of concatenated contingency tables enabled identification of the most important features for both the younger and older inhabitants of selected countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 34-48
Keywords: analiza korespondencji; pokolenia; correspondence analysis; generation